Identification of protein complexes of microsomes in rat adipocytes by native gel coupled with LC-ESI-QTOF. Issue 4 (17th February 2016) - Ke, Ming; Zhang, Yongqian; Xiong, Yan; Saeed, Yasmeen; Deng, Yulin
Abstract : The study of the composition of microsome proteins/complexes/interactions in adipocytes provides useful information for researchers related to energy metabolism disorders. Abstract : The study of the composition of microsome proteins/complexes/interactions in adipocytes provides useful information for researchers related to energy metabolism disorders. The native gel coupled with LC-ESI-QTOF approach was employed here for separating protein complexes. We found a series of proteins functionally clustered in biological processes of protein metabolism, cellular carbohydrate catabolism, response to stimulus and wounding, macromolecular complex subunit organization, positive regulation of molecular function, regulation of programmed cell death and biomolecule transport. According to clustering of proteins' electrophoresis profiles across native gel fractions and bioinformatics data retrieval, protein complexes/interactions involved in protein metabolism, cellular carbohydrate catabolism, macromolecular complex subunit organization and biomolecule transport were identified. Besides, the results also revealed some functional linkages, which may provide useful information for discovering previously unknown interactions. The interaction between SSAO and ALDH2 was verified by co-immunoprecipitation. The native gel combining mass spectrometry approach appeared to be a useful tool for investigating microsome proteins and complexes to complement the traditional electrophoresis approaches. The native gel strategy together with our findings should facilitate future studies of the composition of rat adipocyte microsome protein complexes under different conditions.